The Relationship Between Career Aspirations and Self-Regulation on Self-Perceived Employability Among Students - Kiani, Pariz (Program Studi Bimbingan Konseling Islam Fakultas Dakwah dan Komunikasi Institut Agama Islam Hamzanwadi NW Pancor, 2025)
The purpose of study to examine the relationship between career aspirations and self-regulation on self-perceived employability among students. Career aspirations refer to an individual's expectations regarding the job they wish to achieve in the future. Self-perceived employability refers to an individual's belief in their opportunities in the job market. Self-regulation plays a role in controlling thoughts, emotions, and actions to achieve career goals. This study employs a quantitative approach with a correlational design. The population consists of 300 students, with a sample of 99 students selected using a simple random sampling technique. Data were collected using three questionnaires: the Career Aspirations Scale, the Self-Regulation Scale, and the Self-Perceived Employability Scale. The data were analyzed using multiple linear regression. The results indicate that career aspirations have a positive relationship with self-perceived employability, whereas self-regulation does not have a direct relationship with self-perceived employability. However, career aspirations and self-regulation remain interconnected in supporting students' readiness for the workforce